Serum IgG level in autoimmune liver diseases and its significance: Is there a need to revisit existing criteria? Experience from a tertiary care center - Annapoorani Varadarajan; Archana Rastogi; Rakhi Maiwall; Chaggan Bihari; Sherin Thomas; Saggere Muralikrishna Shasthry (Indian Journal of Pathology and Microbiology)
Background: Serum immunoglobulin G (IgG) level is elevated in autoimmune liver diseases (AILDs), especially autoimmune hepatitis (AIH). However, its utility is limited in current practice as different criteria propose different cut-off values leading to considerable ambiguity. Materials and Methods: A cross-sectional study was conducted among patients with AILD who underwent a liver biopsy over a ten-year period. From 17644 liver biopsies, 630 patients were included and divided into three groups—AIH (455 patients), primary biliary cholangitis (PBC) (97 patients), and overlap (78 patients). Clinical and laboratory details were collected and histological findings were reviewed. Non-cirrhotic non-alcoholic steatohepatitis (NASH) cases were taken as the control group for IgG level comparison. Results: Among AIH patients, IgG values of >2 times the upper limit of normal (ULN) were associated with significant elevation of aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), bilirubin, and necroinflammatory activity. IgG level of >1.1 times ULN lacks specificity in differentiating AIH from the control group. The receiver operating characteristic (ROC) curve demonstrates maximum sensitivity and specificity at a cut-off value of >1.3 times ULN. Conclusion: Serum IgG cut-off value for diagnosing AIH, either in isolation or as a component of overlap syndrome, needs revision and uniformity. IgG value of >2 times ULN in AIH is associated with severe AIH. A new cut-off value of >1.3 times ULN is proposed.